Evaluation of the Development Level of Low-Carbon Tourism in Chinese Cities - Mao, Shuai; Li, Haihong; Cai, Xiang; Liu, Fengqin; Zhong, Hong; Song, Yang (Frontiers in Environmental Science, 2022)
Low-carbon tourism reflects the degree of environmental concern in the tourism industry and is also the foundation of green, sustainable, and ecological tourism. The transformation of the tourism industry, known as the sunrise industry, to a low-carbon pattern contributes to the sustainable development of tourism cities. In this study, an objective evaluation indicator system for low-carbon tourism cities is constructed from the three dimensions of economy, environment, and society, followed by the determination of the weights of the evaluation indicators using an analytic network process model. Ten low-carbon pilot cities in China are evaluated using statistical data of 2014 and 2019. The main research results show that when a city’s economy has reached a certain level, with the development of the economy and individuals’ income and the gradual reduction in environmental pollution, the city’s development level of low-carbon tourism will also be better. Moreover, although these ten low-carbon pilot cities have similar development levels in terms of their social dimension, they have differed greatly in their economic and environmental dimensions. The tourism cities with better economic development levels also rank higher in terms of low-carbon environment and ecological environment, and the overall development level of low-carbon tourism is also better, which shows the obvious Matthew effect as a whole. This study contributes a set of objective evaluation index systems in line with the connotation of low-carbon tourism and assesses the dynamic difference between the cities. This study provides targeted policy recommendations for the construction of low-carbon tourism cities in China.